7(x+5)=2(x+6)(3-1)

Simple and best practice solution for 7(x+5)=2(x+6)(3-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x+5)=2(x+6)(3-1) equation:



7(x+5)=2(x+6)(3-1)
We move all terms to the left:
7(x+5)-(2(x+6)(3-1))=0
We add all the numbers together, and all the variables
7(x+5)-(2(x+6)2)=0
We multiply parentheses
7x-(2(x+6)2)+35=0
We calculate terms in parentheses: -(2(x+6)2), so:
2(x+6)2
We multiply parentheses
4x+24
Back to the equation:
-(4x+24)
We get rid of parentheses
7x-4x-24+35=0
We add all the numbers together, and all the variables
3x+11=0
We move all terms containing x to the left, all other terms to the right
3x=-11
x=-11/3
x=-3+2/3

See similar equations:

| -10+7x=5x+8 | | 19000=x+.02x | | 7u/5=-14 | | 19000=x+02x | | (15/65)=2^(t/2) | | 10^(x+4)=7^(2x) | | 19000=(x×.02)+x | | 7v+4+45=10v+22 | | 10x-8=5x-13 | | 9s-13+14s=20s+5 | | x3-3x2-8=0 | | x3+3x2-8=0 | | 20=4/5r | | |3y+1|=2y-4 | | 4—³x=256 | | 0.06n-0.3=-0.2@ | | (4x-10)°=x | | -6(w+20)=42 | | 16+n=20 | | 7y-4+3y+6=9y+18 | | -2(-2x-3)=2x+6 | | −8=  16−2n16−2n | | 6t+13=-53 | | 3=d+7/8 | | 19–x=25 | | −12x+4=  −7x−16−7x−16 | | 3x-49x+176x-31=180 | | –3q−10=–5q | | 2^(x+2)=(1/23) | | 4(x+4)+2=2(x+9)=2x | | 7x+15=65 | | 5x-4=129 |

Equations solver categories